2009
DOI: 10.1007/s10668-009-9221-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental self-efficacy, attitude and behavior among small scale farmers in Zambia

Abstract: The rural livelihood system in Zambia is essentially agriculture, and agriculture is the main link between people and their environment. Through agricultural activities, people seek to husband the available soil, water and biological resources so as to 'harvest' a livelihood for themselves. The aim of this study is to examine Zambian farmers' awareness and attitude toward the degradation of the environment and their relationships with a set of beliefs to evaluate their perceived capacity to take actions to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…Environmental self-efficacy was measured on a scale adapted from Wu and Mweemba (2010). This scale consists of 4 items.…”
Section: Instrumentmentioning
confidence: 99%
“…Environmental self-efficacy was measured on a scale adapted from Wu and Mweemba (2010). This scale consists of 4 items.…”
Section: Instrumentmentioning
confidence: 99%
“…Following Ostrom (1999), people's interest in conserving forest remains low as long as populations do not place strong importance on the forest for their daily livelihoods. Another hypothesis states that with the awareness about the growing scarcity of resources, the interest in conserving them will grow (Behera 2009, Wu andMweemba 2010). Based on these hypotheses we pursued three research objectives: (i) to develop a methodology that would measure the importance of forest fragments and Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…On the organizational side, it also related to the centralized planning and decisionmaking process in one program, where community participation was more a process of information giving rather than an opportunity for meaningful participation by affected households. Elsewhere, self-efficacy has been found to be important in promoting program participation in rural farming communities (Wu & Mweemba, 2010). In a realist synthesis of welfare programs, Pawson (2002) found that bureaucratic impediments and poor communication processes prevented those most in need of accessing services, often because of limited human capital and poor self-efficacy.…”
Section: Bureaucratic Impedimentsmentioning
confidence: 99%
“…In other words, based on an assessment of the risk, they often felt that they could not experiment with new crops or methods, as failure would be catastrophic. This has been identified as a common constraint for subsistence farming families (Alexander, Moglia, & Miller, 2010;Rodgers, 1995;Todaro, 2009;Vazquez Barquero, 2010;Wu & Mweemba, 2010). This again relates to the concept of self and task-efficacy (Vazquez Barquero, 2010); and has been found to play a significant role in decisions to change farming practices (Sen, 2001;Todaro, 2009;Wu & Mweemba, 2010).…”
Section: Access To Livelihood Assetsmentioning
confidence: 99%
See 1 more Smart Citation